The Effect of Product Quality and Service Quality on Customer Satisfaction of Nazar Paint Wall Paint Bandung - Muhamad Syaiful Islam; Nugraha Saefudin (Dinasti Review, 2026)
The purpose of this research is to identify the factors influencing Nazar Paint wall paint customers' happiness in Bandung, Indonesia, with respect to the product and service quality. Customer complaints about product and service quality are one of the important topics that formed the basis of this study. The study makes use of a quantitative technique that combines descriptive and verification techniques. The data was gathered by sending out surveys to one hundred people who had bought and used wall paint from Nazar Paint. Several statistical tests, including multiple linear regression, the F-test, and the t-test, were used to examine the data. The research found that customer satisfaction is positively and significantly impacted by both product and service quality, either singly or in combination. If the Nazar Paint wall paint business unit in Bandung wants to keep its customers happy, it should follow these recommendations and make their products more consistent and their services better.